Factors Associated with Anemia among People Living with HIV/AIDS Taking ART in Ethiopia - Ketema Bizuwork Gebremedhin; Tadesse Bedada Haye (Advances in Hematology)
Background. Globally, anemia, among people living with HIV/AIDS, is a major public health problem. It has a significant effect on the progression of HIV/AIDS to advanced stages and there are a number of factors that often affect anemia. However, there is little insight regarding factors affecting anemia among HIV/AIDS patients in developing countries, including Ethiopia. Objective. This study aimed at investigating factors affecting anemia among people living with HIV/AIDS taking ART drug at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Methods. A hospital based cross-sectional study design was used to assess factors affecting anemia among people living with HIV/AIDS. Structured checklist was used to gather information from charts of patients selected by simple random sampling method. We analyzed the data to identify factors associated with anemia among people with HIV/AIDS using logistic regression models. Results. A total of 301 selected charts were reviewed. The median age was 38 ± 10.38. The majority (62.5%) of the patients were taking ZDV-containing ART drug (ZDV/3TC/NVP). The overall anemia prevalence was 34.6%, while about 5%, 15.6%, and 14% of the patients had severe, moderate, and mild prevalence of anemia, respectively. Factors that were found to affect anemia among these patients include gender (OR = 2.26 [95% CI: 1.22, 4.16]), occupation (OR: 0.57 [95%CI: 0.35, 0.92]), WBC count (OR = 2.30 [95% CI: 1.29, 4.09]), platelet count (OR = 2.89 [95% CI: 0.99, 8.41]), nutritional status (OR = 2.05 [95% CI: 0.69, 6.02]), and WHO clinical stage of HIV/AIDS (OR = 3.69 [95% CI: 1.86, 7.31]). Conclusions. About one in three patients was found to be anemic. Intervention aimed at diagnosing and treating anemia among people living with HIV/AIDS should be considered.